2005
DOI: 10.1111/j.1365-277x.2004.00581.x
|View full text |Cite
|
Sign up to set email alerts
|

Patient‐centred outcomes in dietary research

Abstract: Should address the issue of patient involvement in the determination of outcome and how this then influences future care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
8

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 43 publications
(54 reference statements)
0
17
0
8
Order By: Relevance
“…However, most studies focus on measurable health outcomes, such as weight loss and change in body fat percentage, and there is little information about how clients attending lifestyle modification programs view the outcomes and how such programs impact upon their lifestyle and behavior. Although it has been recognized that the views of the client should be included in outcome measurement [17], little information is available in the literature related to client involvement in evaluating the outcomes of lifestyle modification programs [18,19]. The purpose of this study was to obtain views of clients attending a community based LMP on lifestyle and behavior change, in order to facilitate continuing development of the whole service in supporting individuals to make sustainable lifestyle changes.…”
Section: Introductionmentioning
confidence: 99%
“…However, most studies focus on measurable health outcomes, such as weight loss and change in body fat percentage, and there is little information about how clients attending lifestyle modification programs view the outcomes and how such programs impact upon their lifestyle and behavior. Although it has been recognized that the views of the client should be included in outcome measurement [17], little information is available in the literature related to client involvement in evaluating the outcomes of lifestyle modification programs [18,19]. The purpose of this study was to obtain views of clients attending a community based LMP on lifestyle and behavior change, in order to facilitate continuing development of the whole service in supporting individuals to make sustainable lifestyle changes.…”
Section: Introductionmentioning
confidence: 99%
“…Ascertaining the satisfaction with provided health services is essential for continuously improving the quality of health care. This validated outpatient survey provides an assessment tool suitable for both research (Jackson et al. , 2005) and clinical care purposes (Kippie & Lyon, 1999; Isenring et al.…”
Section: Discussionmentioning
confidence: 99%
“…During secondary school spending pocket money on cigarettes and alcohol becomes more frequent. However 2017 study Youngster`s life quality and healthy lifestyle aspects in Kurzeme and Liepaja shows that there are more smokers in eighth grade (78%), smoking frequency varies -20% admits that they are regular smokers (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) cigarettes per day. In comparison with 2008, where 52.6% boys and 51.4% girls had encountered alcohol abuse, but at twelve grade -76.7% boys and 73.7% girls, 2017 study revealed that at least 89% ninth graders and 73% secondary school students had consumed alcohol "because others in the group were drinking", which can be explained by the fact that usually motivated, success-oriented students continue studies in secondary school, while part of the ninth graders continue their education at vocational schools or find job.…”
Section: Methodsmentioning
confidence: 99%
“…Siekierski and Ponchio (2014) emphasize that according to studies where demand for uptake of nutrients is simulated (Behrman, Deolalikar, 1990;Barrett, 2002) and according the studies about link between food choices and health and labour market (Pitt et al, 1990), as well as body weight (Cawley, 2004;Cutler et al, 2003), food in economy is both commodity and investment, because with taste, texture and feeling of satiety food gives instant satisfaction, but it is also related with health and wellbeing, costs and benefits. Since food is essential part of quality of life and unhealthy nourishment can leave a negative effect on health (Jackson et al, 2005), along with growing public concerns about eating habits more and more discussions occur on necessity to increase the proportion of health education in educational programs in Latvia, as well as on requirements for food quality in educational …”
Section: Introductionmentioning
confidence: 99%